Implementasi Pembiasaan Membaca Asmaul Husna terhadap Kemampuan Hafalan Al–Qur’an Juz 30 Anak - Anak Majlis Ta’lim Milatul Fikriah - Sihabudin Sihabudin; Ajat Rukajat; Khalid Ramdhani (ISLAMIKA, 2022)
This study aims to find out how the implementation of the habit of reading Asmaul Husna before sunset in improving the ability to memorize Al - Qur'an children of Majis Ta'lim Milatul Fikriah West Karawang. By going through the method of reading Asmaul Husna, children will be better able and familiar with rote memorization, especially those written in Arabic, such as prayers, Hadiths of the Prophet SAW and others. This research design uses a qualitative approach, with data collection methods, namely: 1) observation 2) interviews 3) documentation. While the data analysis used the Miles Huberman model with three stages of analysis, namely: 1) data reduction 2) data presentation 3) conclusion drawing. The results showed that 1) the habit of reading Asmaul Husa was carried out at the time of sunset and direct guidance by the teaching ustadz little by little. So that the rhythm or tone in the reading of Asmaulhusan is in harmony with the game taught by the ustadz at the Majlis Ta'lim Milaul Fikriah, West Karawang; 2) through the application of the Asmul Husna reading habituation method, it has an influence in increasing the children's hadafal al qur'an abilities in the milatul fikriah congregational masjlis. And it also has an impact on children's morals and character, such as being more polite to their parents and respecting their peers; 3). The supporting factors that influence are the role of teachers and parents, the enthusiasm of students, and the rhythm, tone or style that is read. As for the inhibiting factor is a sense of laziness and children who tend to be carried away by bad themes,